The impact of Environmental Education (EE) on the society’s awareness, responsibility, and attitude towards the development of a lifelong attitude of pro-conservation behaviour in Kota Kinabalu, Sabah - E F Charlie; Muhamad Suhaimi Taat; M N Nordin; Fiffy Hanisdah Saikim (IOP Publishing Ltd., 2021)
The deterioration of our environmental conditions is caused by human behaviour. It is a fact that our environment and ecosystem suffered a tremendous amount of exploitation and extinction due to human's greed and ignorance. This research aims to identify the impacts of Environmental Education (EE) among Kota Kinabalu, Sabah, and to identify the significant difference and significance correlation on their awareness, responsibility, and attitude to a lifelong attitude of pro-conservation behaviour. The questionnaire is used as a research instrument and SPSS analyses the data. Mean; SD; t-test and Pearson coefficient of correlation was the statistical techniques used to analyze the data and Leximancer software used for the content analysis. A total of 500 respondents participated in the survey, and 20 respondents were interviewed. In this study, EE has effectively raised the student's environmental awareness, but relatively ineffective in changing their behaviour. The results revealed that there was a significant difference based on demographic aspects from the data collected. The results via statistical package for the social sciences (SPSS) revealed that there was a significant positive correlation on society's awareness (r= .351), responsibility (r= .484) and attitude (r= .552) with pro-conservation behaviour from the data collected. The society's awareness, responsibility, attitude, and behaviour towards conservation are essential and needed more attention from various parties to develop a lifelong attitude towards environment and biodiversity conservation. It is hoped that this study's findings will be beneficial in providing information and guidelines for more effective planning of EE programmes in the future.